Preclinical approaches to studying liver and kidney fibrosis: models and methodologies - Tiwari, Abhilasha; Singh, Shivam; Sharma, Rajesh Kumar; Kumar, Sandeep (Frontiers in Pharmacology, 2026)
Organ fibrosis, notably affecting the liver and kidneys, remains a major contributor to global morbidity. This review examines the pathophysiology, molecular mechanisms, and preclinical models used to study hepatic and renal fibrosis. In liver fibrosis, hepatic stellate cell activation, chronic inflammation, and extracellular matrix accumulation are central features, while renal fibrosis involves myofibroblast activation and redox-mediated signaling pathways. The present review highlights both in vitro and in vivo models such as the carbon tetrachloride, bile duct ligation, and dimethylnitrosamine-induced liver fibrosis models, as well as renal fibrosis models like unilateral ureteral obstruction (UUO), subtotal nephrectomy, and adriamycin nephropathy. It also emphasizes advanced experimental platforms including liver slice systems and stem cell transplantation techniques. All these above-mentioned models of hepatic and renal fibrosis involve immune cells directly or indirectly, e.g., cytokines, chemokines, and growth-promoting factors in renal fibrosis UUO model. By integrating molecular insights and experimental techniques, this review provides a comprehensive guide for future therapeutic strategies aimed at mitigating fibrosis in chronic liver and kidney diseases.